The reasons for delay lumbar puncture - MH. Lotfi (The Journal of Qazvin University of Medical Sciences, 2017)
Early diagnosis of meningitis and encephalitis and prompt initiation of appropriate therapy is vital and any delay will lead to high mortality and serious and permanent morbidity. The main purpose of this study was to evaluate the management of 220 patients with suspected central nervous system (CNS) infections (meningitis and encephalitis) to determine the percentage of patients’ suspected CNS infection undergo lumbar puncture in acceptable time (in accordance with conventional algorithms). In this descriptive study, patients with suspected CNS infections admitted to Bu-Ali and Qods hospitals, in the period July 2013 to December 2015 were studied. Information of 220 patients was collected. Continuous variables were summarized as means ± standard deviation and categorical variables as frequencies and percentages. Lumbar puncture (LP) in patients was delayed in 200 cases (91%). Most common causes of delay in performing LP were prolongation of the process of determining patient needs to puncture, satisfying patients, CT scan delay and the delay in allowing LP by neurologist. In this study, delaying LP rate was higher than other studies. It seems certain pattern in assistants’ visits for counseling. CT requests and neurologic consultation before LP performed for all adult patients.